Hierarchical MoS2@Polypyrrole core-shell microspheres with enhanced electrochemical performances for lithium storage. (10th April 2018) - Xie, Dong; Zhang, Min; Cheng, Faliang; Fan, Hongbo; Xie, Shilei; Liu, Peng; Tu, Jiangping
Abstract: Advanced anode materials for lithium ion batteries are central to the area of electrical energy storage devices. Herein, we have developed a two-step strategy for synthesizing MoS2 @polypyrrole (MoS2 @PPY) core-shell microspheres. In such a novel architecture, the MoS2 microspheres are homogeneously wrapped by conductive polypyrrole coating forming core-shell microspheres. As a preliminary test, the obtained MoS2 @PPY microspheres exhibit greatly enhanced electrochemical performances for lithium storage compared with un-modified MoS2 microspheres. The MoS2 @PPY microsphere electrode displays a high specific capacity of 1012 mAh g −1 after 200 cycles at 200 mA g −1 and high rate performance (600 mAh g −1 at 4000 mA g −1 ). The superior electrochemical performances are attributed to the advantageous combination of hierarchical microsphere structure and conductive PPY coating. Graphical abstract: Hierarchical microsphere structure and conductive PPY protective shell are realized in the MoS2 @PPY core-shell microspheres via combined hydrothermal and self-polymerization approaches, which exhibit superior lithium storage performances. Highlights: MoS2 @PPY core-shell microspheres were synthesized. Hierarchical microsphere structure and conductive PPY protective shell are realized. Reversible capacity of MoS2 @PPY electrodes can maintain 1012 mAh g −1 after 200 cycles at 0.2 A g −1 . MoS2 @PPY electrodes exhibit superior electrochemical performances than bare MoS2 electrodes.